2013
DOI: 10.1103/physrevb.87.075304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of symmetry reduction on the spin dynamics of (001)-oriented GaAs quantum wells

Abstract: Spin quantum beat spectroscopy is employed to investigate the in-plane anisotropy of the spin dynamics in (001) GaAs/AlGaAs quantum wells induced by an external electric field. This technique allows the anisotropy of the spin relaxation rate s and the electron Landé g factor g * to be measured simultaneously. The measurements are compared to similar data from (001) GaAs/AlGaAs quantum wells with applied shear strain and asymmetric barrier growth. All of these operations act to reduce the symmetry compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Regarding the former, Karimov et al reported a calculation result that τ s is reduced to 1/30 by introducing an interface compositional gradient layer with the thickness of two monolayers [ 35 ]. In contrast, it is reported that the Rashba split energy that induces in-plane B eff is negligibly small for the MQW having compositional variations, which means that τ s is not modulated [ 36 , 37 ]. Since whether the compositional gradient layers are present or not is not sure in our samples, we do not mention their effects on τ s .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the former, Karimov et al reported a calculation result that τ s is reduced to 1/30 by introducing an interface compositional gradient layer with the thickness of two monolayers [ 35 ]. In contrast, it is reported that the Rashba split energy that induces in-plane B eff is negligibly small for the MQW having compositional variations, which means that τ s is not modulated [ 36 , 37 ]. Since whether the compositional gradient layers are present or not is not sure in our samples, we do not mention their effects on τ s .…”
Section: Resultsmentioning
confidence: 99%
“…The systematic search for symmetries and constants of motion exhibited by the Hamiltonian model is reported in Section 3 . A similar route has recently been used to investigate the dynamics of a pair [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ] or a chain [ 32 , 33 ] of coupled spins (also greater than ) subjected to time-independent and time-dependent [ 34 , 35 , 36 ] external magnetic fields. Symmetry arguments have also been exploited to elegantly bring to light intriguing dynamic features of physical systems living in Hilbert spaces of infinite dimensions [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34] A reduction of the symmetry of the system leads to an anisotropic Zeeman splitting of electrons for different in-plane directions of B. [35][36][37][38][39] On the one hand, low-symmetry growth directions cause a slight anisotropy of the diagonal components g xx = g yy . 35 On the other hand, due to asymmetric band-edge profiles small off-diagonal components g xy = g yx = 0 arise while g xx = g yy .…”
Section: Introductionmentioning
confidence: 99%
“…35 On the other hand, due to asymmetric band-edge profiles small off-diagonal components g xy = g yx = 0 arise while g xx = g yy . [36][37][38][39][40] Remarkably, the g factor in spin-3/2 hole systems shows a strong dependence on the direction of B. The Zeeman splitting can differ by an order of magnitude for the in-plane and out-of-plane directions of B.…”
Section: Introductionmentioning
confidence: 99%